Cytoprotective Effect of Astaxanthin in a Model of Normal Intraocular Pressure Glaucoma - Kasumi Kikuchi; Zhenyu Dong; Yasuhiro Shinmei; Miyuki Murata; Atsuhiro Kanda; Kosuke Noda; Takayuki Harada; Susumu Ishida (Journal of Ophthalmology)
Glaucoma is characterized by axonal degeneration of retinal ganglion cells (RGCs) and apoptotic death of their cell bodies. Lowering intraocular pressure is currently the only way to treat glaucoma, but it is often insufficient to inhibit the progression of the disease. Glaucoma is a multifactorial disease, and the involvement of oxidative stress has recently received much attention. In the present study, we investigated the cytoprotective effect of astaxanthin (AST) on RGC degeneration using a normal-tension glaucoma (NTG) mouse model, which lacks the glutamate/aspartate transporter (Glast) and demonstrates spontaneous RGC and optic nerve degeneration without elevated intraocular pressure. Three-week-old Glast± mice were given intraperitoneal injections of AST at 10, 30, or 60 mg/kg/day or vehicle alone, and littermate control mice were given vehicle alone for 14 days, respectively. Five weeks after birth, the number of RGCs was counted in paraffin sections of retinal tissues stained with hematoxylin and eosin. We also used a retrograde labeling technique to quantify the number of RGCs. Additionally, the phosphorylated (p) IκB/total IκB ratio and the 4-hydroxynonenal (HNE) were measured in retinal tissues. The number of RGCs in Glast± mice was significantly decreased compared with that in control mice. RGC loss was suppressed by the administration of AST at 60 mg/kg/day, compared with vehicle alone. Following AST administration, the concentration of 4-HNE in the retina was also suppressed, but the pIκB/IκB ratio did not change. Our study revealed that the antioxidative stress effects of AST inhibit RGC degeneration in the retina and may be useful in the treatment of NTG.